(untitled) (The South Asianist Journal, 2016)
The nineteenth-century priest of the Kālī temple at the village of Dakṣiṇeśvar near Calcutta, Rāmakṛṣṇa Paramahaṁsa, has been famous for his frequent bhava [emotional state or mood] or ecstasy, and samādhi or syncope [temporary loss of consciousness], believed to be a fallout of his divine madness [divyonmattata]. This madness is not to be understood as mental derangement but as a respectable erratic behaviour culturally associated with the state of a mystic. The Hindu Bhakti [devotional] movement produced numerous saints who appear, from the standpoint of society, as ‘crazy’, because of their indifference to the phenomenal world. In fact, Rāmakṛṣṇa consciously and forcefully imitated the reported ecstatic (and erratic) behaviour of Śrī Caitanya. This paper offers a critique of the pious and hagiographical accretions of the master’s divine madness and explores the motivations and modalities of his frequent withdrawal from the sensate world in large gatherings or in small groups, there being no clear or attestable account of his samādhi when no onlooker was around. Rāmakṛṣṇa’s reminiscence of his lone attempted suicide in the temple sanctum, thwarted by an epiphany, has been colourfully crafted and carefully circulated by his disciple biographer Svāmī Sāradānanda, but duly debunked by the saint’s famous record-keeper and biographer Mahendranāth Gupta. This paper thus mines the vernacular texts in search of the making of a Hindu mystic.